2004
DOI: 10.1097/01.nmd.0000130135.78017.96
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity of Medical Illnesses Among Adults With Serious Mental Illness Who Are Receiving Community Psychiatric Services

Abstract: We studied the medical comorbidity among individuals with serious mental illness who were receiving community-based psychiatric treatment. A total of 200 psychiatric outpatients divided between those with schizophrenia and affective disorder diagnoses were recruited from samples receiving outpatient care at two psychiatric centers. Interviews used questions from national health surveys. Logistic regression analyses compared responses from each sample with those of matched subsets of individuals from the genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
205
3
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 287 publications
(228 citation statements)
references
References 14 publications
14
205
3
3
Order By: Relevance
“…2,5 Much of the disability in patients with mental disorders is attributed to co-occurring general medical conditions. 6 Many of these conditions, notably diabetes (28%), hypertension (30%), and hyperlipidemia (23%), occur more frequently in patients with mental disorders than non-psychiatric patients 7 and are the leading risk factors for cardiovascular disease [CVD] 8 . CVD is the most common condition associated with premature death in patients with mental disorders.…”
Section: Introductionmentioning
confidence: 99%
“…2,5 Much of the disability in patients with mental disorders is attributed to co-occurring general medical conditions. 6 Many of these conditions, notably diabetes (28%), hypertension (30%), and hyperlipidemia (23%), occur more frequently in patients with mental disorders than non-psychiatric patients 7 and are the leading risk factors for cardiovascular disease [CVD] 8 . CVD is the most common condition associated with premature death in patients with mental disorders.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] There is evidence that even if individuals with serious mental illness have a regular source of primary care, they may not access services because of a lack of coordination between mental and medical health care. 4,5 Primary care is of value to patients with behavioral disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Jones et al analyzed Medicaid claims data for 147 individuals with severe mental illness and found that 74 percent had one diagnosis of chronic health problems, while 50 percent had two or more diagnoses [8]. Sokal et al studied 200 psychiatric outpatients with schizophrenia and affective disorders and found that they had significantly elevated odds of diabetes, lung diseases, and liver problems compared with matched subsets of individuals from the general population [9]. All of these medical conditions may be related to impaired physical and social role functioning and lowered rates of labor force participation.…”
Section: Introductionmentioning
confidence: 99%